MENELUSURI PERKEMBANGAN TEORI KEKAYAAN MEDIA - Antar Venus; Nantia Rena Munggaran (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
The medium in this theory is defined as any form of communication channels is one of the very important elements of communication. Our ability to choose the appropriate media in conveying the message would determine the performance or effectiveness we divide the message to others. Media richness theory (TKM) said that not every media match with any kind of task or message would we send. Each media has its advantages and disadvantages of each. Rich media is suitable for its high equivocality task types, whereas a poor media (Lean media) matches tugs or message that has a low equivocality. The more a potential message multiple interpretations (equivocal), is uncertain, then the strategic nature required an increasingly rich media. Daft and Lengel According to media, wealth can be measured by four criteria: (1) the ability to convey variety of instructions; (2) The immediacy of feedback; (3) the ability to present a variety of study; and finally the ability to 'personalize' the message to the recipient.